The kindling - Bell, Braden (Middle school magic, 2012)
When unusual powers kindle inside them, Conner, Lexa, and Melanie discover that their teachers are powerful magi too and the students are exhilarated to add fighting evil to their daily classes--until the dark forces of the Umbra kidnap Melanie's young sister as part of a grotesque experiment.